2006
DOI: 10.1111/j.1365-2133.2006.07213.x
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal wrist movements are correlated with objective clinical scores and plasma chemokine levels in children with atopic dermatitis

Abstract: This is the first study to demonstrate that wrist activities, nonintrusively measured by the DigiTrac monitor at home, are closely correlated with the objective clinical scores and levels of peripheral blood chemokine markers for AD but not with the reported symptoms of pruritus or sleep loss. We propose that wrist activities between 1 and 3 Hz for the first 3 h are a good indicator of AD severity in children and should substitute for the pruritus and sleep-loss components of the SCORAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
92
2
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(98 citation statements)
references
References 20 publications
3
92
2
1
Order By: Relevance
“…In previous studies, we also documented that AD-associated chemokine levels (cutaneous T-cell attracting chemokine, macrophage-derived chemokine and thymus and activation-regulated chemokine, all being type 2 T-helper lymphocytespecific chemokines) [19,20] and nocturnal wrist activities (as a surrogate marker of itching) [21] correlated with the extent and the intensity components of SCORAD, but not with subjective symptoms of pruritus or sleep loss. This implies that subjective evaluation and objective status are separately entities.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…In previous studies, we also documented that AD-associated chemokine levels (cutaneous T-cell attracting chemokine, macrophage-derived chemokine and thymus and activation-regulated chemokine, all being type 2 T-helper lymphocytespecific chemokines) [19,20] and nocturnal wrist activities (as a surrogate marker of itching) [21] correlated with the extent and the intensity components of SCORAD, but not with subjective symptoms of pruritus or sleep loss. This implies that subjective evaluation and objective status are separately entities.…”
Section: Discussionmentioning
confidence: 51%
“…A HON index of (Obj 1, N 1) is defined as a patient with mild acute and chronic severity, whereas HON (Obj 3, N1) may represent a patient with mild disease over the past 12 months but recent acute exacerbation. Pruritus [21] and sleep disturbance [22] can also be objectively evaluated and documented with the optional portion of the HON classification. In this regard, a HON index of (Obj 1, N1, 40 g min )1 , 90%) represents a patient with mild acute and chronic severity, average wrist movement of 40 g min )1 and sleep efficiency of 90%; whereas HON (Obj 3, N3, 200 g min )1 , 75%) represents a miserable patient with severe disease, intense nocturnal itch and much sleep disturbance.…”
Section: Discussionmentioning
confidence: 99%
“…The different sleeping environments and the attachment of numerous leads and equipment to the patient in the PSG setting could also cause irritation of the skin or other discomfort for the patient with AD, and thus their home sleeping conditions might not be truly reflected. In contrast, actigraphy, a small, wrist-worn device that estimates sleep-wake patterns by using activity-based monitoring, has increasingly been used in recent years for delineating sleep patterns 26,27 because of its ease of use, especially for the pediatric population, 25,28,29 but its validation with PSG measurements in children with AD had not been established. Our study is the first to demonstrate a good correlation of results by actigraphy and PSG in this patient group, and we suggest that actigraphy is a good alternative for further sleep studies in children with AD.…”
Section: Discussionmentioning
confidence: 99%
“…13,19,[21][22][23][24][25][26] This study revealed moderately strong correlations between actigraphy scores and both the scratching index and PSG scores, which included sleep latency, sleep efficiency, and stage-2 sleep. Although actigraphy has been presented both as a measure of scratching 20 and sleep, 13 the study by Benjamin et al 20 revealed that actigraphy recordings were significantly and highly correlated with video-recording measures of sleep, scratching, and restlessness.…”
Section: Discussionmentioning
confidence: 99%